Investigating the demographic characteristics of institutional investors affecting representativeness, conservatism and overconfidence biases in their individual investments - KOÇ, İDİL ÖZLEM (My University, 2021)
This study aims to identify the factors affecting representativeness, conservatism, and overconfidence biases in a sample of Turkish institutional investors. This study is different to other studies in that it focuses on the individual investments of institutional investors in capital markets. The respondents, who were selected via the convenience sampling method, were asked survey questions. In the study, models are formed with the stepwise method using linear regression analysis, and survey questions that represent the examined biases are selected as the dependent variables. The age, gender, marital status, education, having children, and the experience of institutional investors are included in the analysis as the independent variables. This way, we can reveal which of the independent variables are statistically significant and which of the subcategories of the independent variables are most influential on the biases. As a result of the analysis, in addition to determining the variables that affect a single bias, education level affects all examined biases, especially low education, which is higher. In the regression analysis, experience is identified as a significant variable affecting representativeness and conservatism biases. It is observed that the institutional investors who are inexperienced or less experienced interact with these two biases more in their decisions related to their individual investments. Gender is found to be a significant variable on both conservatism and representativeness biases, and female institutional investors are more effective than men on the representativeness and conservatism bias. Furthermore, it is determined that the marital status variable and the divorced institutional investors are significantly influential on conservatism and overconfidence biases.
Keywords: Game Overconfidence bias; Conservatism bias; Representativeness bias; Demographic factors; Institutional investor; Individual investment